PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI PENERAPAN MEDIA KARTU GAMBAR - LAELY, KHUSNUL (Program Studi Magister Pendidikan Anak Usia Dini, 2013)
This study aims to determine whether the media card images can improve the ability toread the beginning of group B Bustanul Athfa ‘Aisyiyah Kalinegoro Mertoyu dan Magelang anddescribe the process of taking the picture card media. This research is a classroom action research.The data was collected by conducting or altests, observation, and field notes. Media used the mediacard image. Analysis of the data using qualitative data analysis and quantitative data analysis. Thisstudy can be useful for students, teachers, early childhood education institutions, and otherresearchers. Benefit for students is that it can activate and focus attention in learning, teachers candevelop learning back to read the beginning according to the stages of child development. For thestudy of early childhood institutions can be input in order to improve the quality of teachingbeginning reading skills, and the benefits to other researchers can conduct research or design inorder to improve the ability to read a more interesting beginning. Beginning reading skillsincreased from 60.48% to 87.38% after applying media card images in learning. This is because theapplication of media images designed card swith cards of different investigator sexisting imageisthe picture card has a large size so that children can observe that sits behind the teacher'sexplanation, but it has interesting pictures and letters inredink the word has so children excited,enthusiastic, and focused on learning. Keywords: Drawing Card, Read the Beginning, and Action Research Penelitian ini bertujuan untuk mengetahui apakah media kartu gambar dapatmeningkatkan kemampuan membaca permulaan kelompok B Bustanul Athfa 'Aisyiyah KalinegoroMertoyudan Magelang. Penelitian ini merupakan penelitian tindakan kelas. Pengumpulan datadilakukan dengan tests, observasi, dan catatan lapangan. Media yang digunakan adalah media kartugambar. Analisis data menggunakan analisis data kualitatif dan kuantitatif. Penelitian ini bergunabagi siswa, guru, lembaga pendidikan anak usia dini, dan peneliti lainnya. Manfaat bagi siswaadalah bahwa hal itu dapat mengaktifkan dan fokus perhatian dalam pembelajaran, guru dapatmengembangkan belajar kembali untuk membaca permulaan sesuai dengan tahapan perkembangananak. Untuk lembaga anak usia dini dapat menjadi masukan dalam rangka meningkatkan kualitaspembelajaran keterampilan membaca permulaan, dan bagi peneliti lain dapat melakukan penelitianatau desain dalam rangka meningkatkan kemampuan membaca permulaan lebih menarik.Keterampilan membaca permulaan meningkat dari 60,48% menjadi 87,38% setelah menerapkanmedia kartu gambar dalam pembelajaran. Penerapan media kartu gambar dirancang berbeda, kartugambar memiliki ukuran yang besar sehingga anak-anak dapat mengamati penjelasan gurumeskipun duduk di belakang, memiliki gambar yang menarik, huruf dan kata sehingga anak-anakbersemangat, antusias, dan terfokus pada belajar. Kata kunci: Kartu gambar, Membaca Permulaan, dan Penelitian Tindakan